2022
DOI: 10.1186/s13046-022-02352-y
|View full text |Cite
|
Sign up to set email alerts
|

The role of TBK1 in cancer pathogenesis and anticancer immunity

Abstract: The TANK-binding kinase 1 (TBK1) is a serine/threonine kinase belonging to the non-canonical inhibitor of nuclear factor-κB (IκB) kinase (IKK) family. TBK1 can be activated by pathogen-associated molecular patterns (PAMPs), inflammatory cytokines, and oncogenic kinases, including activated K-RAS/N-RAS mutants. TBK1 primarily mediates IRF3/7 activation and NF-κB signaling to regulate inflammatory cytokine production and the activation of innate immunity. TBK1 is also involved in the regulation of several other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 278 publications
(398 reference statements)
6
40
1
Order By: Relevance
“…TBK1 was selectively essential in cells that harbor mutant KRAS [42]. Emerging evidence showed that TBK1 plays important role in the pathogenesis of cancer [43][44]. Thus, our ndings suggested that RCC2 could be a novel oncogene in human cancer.…”
Section: Discussionmentioning
confidence: 62%
“…TBK1 was selectively essential in cells that harbor mutant KRAS [42]. Emerging evidence showed that TBK1 plays important role in the pathogenesis of cancer [43][44]. Thus, our ndings suggested that RCC2 could be a novel oncogene in human cancer.…”
Section: Discussionmentioning
confidence: 62%
“…With regard to the TANK-binding kinase 1(TBK1), it was a serine/threonine kinase involved in the induction of IFN-I produce, which was activated by STING1 with being regulated by the second messenger of cGAMP [ 38 , 39 ]. Recent studies suggested that TBK1 exhibited a significant role in mediating the process of survival probability and development in Kras-independent cancer cells [ 40 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…TANK-binding kinase 1 (TBK1) belongs to the non-canonical IκB kinases, and is also known as an NF-κB activating kinase [ 2 ]. TBK1 can be activated by pro-inflammatory cytokines and viral infections.…”
Section: Introductionmentioning
confidence: 99%